Adding value to cereals, roots and tubers (2) - Bruinsma, Domien (Technical Centre for Agricultural and Rural Cooperation, 1999)
This study provides an overview of developments in storage and processing technologies for cereals, roots and tubers in Africa. It also exmamines developments in food marketing chain which may be of economic benefit for producers of these products.